Working Length Changes Following Straight-Line Access and Different Coronal Flaring Methods - Sadeghi, Shiva; Doago, Zeinab (Iranian Endodontic Journal, 2009)
INTRODUCTION: The purpose of this in vitro study was to compare working length (WL) changes after straight-line access (SLA) and different coronal flaring (CF) methods. MATERIALS AND METHODS: Coronal access preparations were made (without SLA) in molar teeth to allow access to 120 canal orifices with a hand file. The suitable cusp and root tips were then flattened to facilitate reproducible and accurate measurements. WL was determined before and after SLA and after different methods of CF. These methods consisted of: stainless-steel (SS) hand files + NiTi hand files, SS hand files + Gates Glidden burs (GG) (#1 to #3), (#3 to #1), GG in step-back manner and crown-down manner without using SS hand files and NiTi rotary orifice shapers. Data was analyzed by paired T-test and coefficient of variance. RESULTS: The mean difference in WL changes after SLA was statistically greater than other methods of CF (P<0.001). The mean difference of WL after CF, in SS hand files + GG (#3 to #1) group was significantly different with SS hand files + NiTi hand files group (P<0.004) and NiTi rotary group (P<0.04). Also the mean changes of WL in SS hand files + NiTi hand files group was significantly different with GG (#1 to #3) group (P<0.01). CONCLUSION: It is better to established working length after SLA. Least changes in WL was occurred with NiTi rotary orifice shapers after coronal flaring.